PROGRESSIVE MUSCLE RELAXATION TO DECREASE NAUSEA AND VOMITING INDUCED CHEMOTHERAPY IN CANCER PATIENTS: A CASE REPORT - Rahayu, Hesti; Endah Panca Lydia Fatma; Elteria Sianturi; Agung Waluyo; Riri Maria; Masfuri; Siti Nurlaelah; Yunisar Gultom (Jurnal Keperawatan Widya Gantari Indonesia, 2025)
Cancer patients usually experience disturbing nausea and vomiting, although they have consumed some medicine before, during, and after chemotherapy. Chemotherapy-induced nausea and Vomiting (CINV) is nausea and vomiting experienced by patients as a result of chemotherapy. CINV is the most significant effect of chemotherapy from the patient’s perspective. CINV is reported as acute, delayed, and combined from both cases. CINV that are not managed properly can cause some problems, such as fluid and electrolyte imbalance, interrupt the next chemotherapy cycle, and decrease productivity and quality of life. Rehospitalization costs caused by CINV in the health care system are high. By the CINV management that is being improved in this time, some patients still experienced nausea and vomiting. Nowadays, non-pharmacological therapy like relaxation techniques is very suggested for patients to relieve CINV. Twenty-five minutes of an audio relaxation technique is effective in decreasing nausea and vomiting in cancer patients. One of the audio relaxation techniques is Progressive Muscle Relaxation (PMR). The case report was taken from one of the type A hospitals in Jakarta, Indonesia . It consisted of 20 cancer patients who underwent chemotherapy. After doing PMR exercise guided by an educational video on a tablet for 4 days after chemotherapy, it was found that there was a 35% decrease in nausea and vomiting scores; they felt comfortable and more relaxed. The interesting educational video of PMR supports the patients to do the exercise well when done in the hospital or at home. Therefore, preventing or reducing the potential problem caused by nausea and vomiting induced by chemotherapy can increase the nursing care quality for the cancer patient. The results of this case report indicate that progressive muscle relaxation can reduce nausea and vomiting due to chemotherapy.